Divalent Metal Ions Mg(2+) and Ca(2+) Have Distinct Effects on Protein Kinase A Activity and Regulation - Knape, Matthias J. (ACS Chem Biol, 2015)
cAMP-dependent protein kinase (PKA) is regulated primarily in response to physiological signals while nucleotides and metals may provide fine-tuning. PKA can use different metal ions for phosphoryl transfer, yet some, like Ca(2+), do not support steady-state catalysis. Fluorescence Polarization (FP) and Surface Plasmon Resonance (SPR) were used to study inhibitor and substrate interactions with PKA. The data illustrate how metals can act differentially as a result of their inherent coordination properties. We found that Ca(2+), in contrast to Mg(2+), does not induce high-affinity binding of PKA to pseudosubstrate inhibitors. However, Ca(2+) works in a single turnover mode to allow for phosphoryl-transfer. Using a novel SPR approach, we were able to directly monitor the interaction of PKA with a substrate in the presence of Mg(2+)ATP. This allows us to depict the entire kinase reaction including complex formation as well as release of the phosphorylated substrate. In contrast to Mg(2+), Ca(2+) apparently slows down the enzymatic reaction. A focus on individual reaction steps revealed that Ca(2+) is not as efficient as Mg(2+) in stabilizing the enzyme:substrate complex. The opposite holds true for product dissociation where Mg(2+) easily releases the phospho-substrate while Ca(2+) traps both reaction products at the active site. This explains the low steady-state activity in the presence of Ca(2+). Furthermore, Ca(2+) is able to modulate kinase activity as well as inhibitor binding even in the presence of Mg(2+). We therefore hypothesize that the physiological metal ions Mg(2+) and Ca(2+) both play a role in kinase activity and regulation. Since PKA is localized close to calcium channels and may render PKA activity susceptible to Ca(2+), our data provide a possible mechanism for novel crosstalk between cAMP and calcium signaling.